EFFECT OF PESTICIDE AND FERTILIZER ON THE SOIL - et. al., Dr. P.Periasamy (International Journal of Modern Agriculture, 2021)
Soil Conservation quality is critical for long-term crop production and biodiversity sustainability. Chemicals and fertilizers are inevitable in modern agriculture. Even though they are still significant assets for universal food security, those negative consequences must be considered, predominantly when justifiable agriculture is the primary goal. Fertilizers and pesticides have a long shelf life in soil and are known to degrade soil quality by killing soil microflora. Microflora present in the soil is an essential constituent of agriculture based environments which helps to boost soil fertility and crop productivity while also regulating simple soil processes. Soil microorganisms are traditionally utilized as bio-indicators present in the soil activity and quality. These factors, beside the special effects of pesticides and fertilizers, such as poisonousness and a change in the soil's substrate availability profile, result in an indirect shift in soil microflora population dynamics. We discuss the long-term effect of fertilizers as well as pesticide practice on cultivated soil microflora in terms of soil quality and viability, soil persistence, and toxicity factors in this paper and the discussion about the possibilities of the alternatives to these chemical pesticides and fertilizers in the near future for lesser harm to the soil and environment